External voting w wyborach bezpośrednich na przykładzie monarchii parlamentarnej Hiszpanii i Republiki Austrii - Bartosik, Patrycja (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The work aims to show the differences in the functioning of the vote on the distance between Spain and Austria. They not without reason have been chosen for this purpose just these two countries. They represent a completely different policy in relation to immigration. The substrate regulations that have been established for citizens living abroad has its origins in the tradition of the country concerned. I draw attention to the difference in access to direct and indirect elections. Refer to the rights and freedoms of every citizen. The aim of my work is to show the light in which were and are now direct elections and the role played. The work includes statistical data.
Keywords: demokracja bezpośrednia; konstytucja; głosowanie korespondencyjne; frekwencja; głosowanie na odległość; wybory; głosowanie